Concise Review: MSC Adhesion Cascade—Insights into Homing and Transendothelial Migration. (3rd April 2017) - Nitzsche, Franziska; Müller, Claudia; Lukomska, Barbara; Jolkkonen, Jukka; Deten, Alexander; Boltze, Johannes
Abstract: Mesenchymal stem cells (MSCs) are promising candidates for adult cell therapies in regenerative medicine. To fully exert their potential, efficient homing and migration toward lesion sites play an important role. Local transplantation deposits MSC in spatial proximity to the lesion, but often requires invasive procedures. Systemic administration routes are favored, but require the targeted extravasation of the circulating MSC at the site of injury. Transplanted MSC can indeed leave the blood flow and transmigrate through the endothelial barrier, and reach the lesion site. However, the underlying processes are not completely dissolved yet. Recent in vitro and in vivo research identified some key molecules scattered light on the extravasation mechanism. This review provides a detailed overview over the current knowledge of MSC transendothelial migration. We use the leukocyte extravasation process as a role model to build a comprehensive concept of MSC egress mechanisms from the blood stream and identified relevant similarities as well as important differences between the extravasation mechanisms. Stem Cells 2017;35:1446–1460